Occurrence of stroke in children and young adults in Indonesia: a multicenter private hospital study - Jeanne Leman; Veli Sungono; Yosua Timotius Haryono; Muhammad Adam Mudzakir; Dewi Lestari Rahmawati; Callistus Bruce Henfry Sulay; Gilbert Sterling Octavius (Clinical and Experimental Pediatrics)
Background Most studies that estimate the occurrence of childhood stroke use heterogeneous methods and rely on International Classification of Diseases codes, a strategy that may be unreliable. Purpose This study aimed to estimate the occurrence of childhood stroke in Indonesia using imaging and clinical data from a private hospital network. Methods This cross-sectional study used consecutive retrospective multicenter data samples collected in 2019– 2023. The study cohort included children aged >28 days to young adults aged 24 years with confirmed ischemic or hemorrhagic stroke on computed tomography (CT) or magnetic resonance imaging (MRI). The 1-year occurrence was calculated, and the data analysis was performed using IBM SPSS Statistics ver. 26.0. Results Over 5 years, the performance of 8,987 CT and 6,133 MRI scans resulted in the identification of 1,074 stroke cases. The average patient age was 14.8±7.0 years. Stroke occurrence was highest in 2021 (9.08%) and lowest in 2022 (5.91%). Male patients accounted for 67.9% of cases, with hemorrhagic strokes accounting for 83.4% of the total, primarily resulting from accidents (73.2%) and predominantly occurring in the frontal region (37.1%). A significant majority of cases (66.7%) were reported in Java. Males had a relative risk of 1.93 (95% confidence interval, 1.48–2.52; P<0.001) for hemorrhagic stroke versus females. Conclusion The incidence of childhood stroke revealed critical epidemiological trends and disparities, emphasizing the need for targeted public health interventions and enhanced stroke prevention strategies in Indonesia.